2012
DOI: 10.1186/1743-7075-9-102
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating ascorbic acid, α-tocopherol, 25-hydroxyvitamin D, and plasma cytokine concentrations in young adults: a cross-sectional study

Abstract: BackgroundInflammation and oxidative stress are associated with the development of numerous chronic diseases. Circulating ascorbic acid, α-tocopherol, and 25-hydroxyvitamin D (25(OH)D) may help reduce concentrations of pro-inflammatory cytokines through their antioxidant and anti-inflammatory properties. These micronutrients may act synergistically, and they may have different anti-inflammatory effects, but previous studies have assessed the link between each of these micronutrients and inflammation in isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Previous studies have recognized the antioxidant and anti-inflamatory properties of ascorbic acid, α-tocopherol [59] and sterols [60]. In our case, the histological and electron microscopy examination revealed that pretreatment with SMSO suppressed the acute hepatic damage and was consistent with the improvement of plasmatic and tissue biological parameters for hepatotoxicity.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have recognized the antioxidant and anti-inflamatory properties of ascorbic acid, α-tocopherol [59] and sterols [60]. In our case, the histological and electron microscopy examination revealed that pretreatment with SMSO suppressed the acute hepatic damage and was consistent with the improvement of plasmatic and tissue biological parameters for hepatotoxicity.…”
Section: Discussionsupporting
confidence: 62%
“…As we indicated earlier, vitamin D deficiency may be linked to low-grade innate immunity-related chronic inflammatory responses6,20,21 known to be associated a range of chronic conditions (including insulin resistance) that predispose individuals to the development of T2DM at a later stage 6,21. As stated above, polymorphisms in CYP27B1 , vitamin D binding protein, and vitamin D receptors – that respectively mediate vitamin D synthesis, transport, and action – disrupt glucose homeostasis and the hormonal action of vitamin D 2226.…”
Section: Resultsmentioning
confidence: 88%
“…Emerging evidence has reported a relationship between vitamin D supplementation and serum levels of proinflammatory and inflammatory markers such as cytokines and CRP. Some studies have reported a positive association with circulation levels of 25(OH)D and others showed an inverse association while some declared no relationship [44][45][46][47].…”
Section: Influence Of Supplementation On Inflammation In Cyp2r1 Variantmentioning
confidence: 99%